A practical approach to the dynamic modelling of an underwater vehicle propeller in all four quadrants of operation. (February 2019) - Tran, Minh; Binns, Jonathan; Chai, Shuhong; Forrest, Alexander L; Nguyen, Hung
This article presents the open water propeller characteristics and the four-quadrant propeller models as applied to a torpedo-shaped underwater vehicle. A series of experiments with a Gavia autonomous underwater vehicle propeller were conducted in the towing tank using a rotor testing apparatus. The purpose of these tests was to measure the propeller thrust and torque under varying flow conditions and then to be used as the basis of the developed propeller models. These mathematical models were constructed using two regression models, a polynomial and a Fourier series. Model coefficients were derived using the method of least squares and a comparison analysis was also conducted to test the robustness of the methodology. Results show that the Fourier series models were able to produce a reasonable and accurate approximation of thrust and torque coefficients with a small number of parameters in the examined condition of this study. The obtained four-quadrant open water characteristics of the autonomous underwater vehicle propeller model would be utilised to improve the system mathematical model for more accurate simulation and controller design, to compare the autonomous underwater vehicle performance equipped with different propulsion units, and to validate computational fluid dynamic results.